Answer:
x = -4/5, y = -6 3/5
Explanation:
The way to use substitution to solve is to isolate (Put it on one side without anything else on that side of the equation) a variable. We can use the first equation to isolate y. We can add y on both sides to get that 2x = y + 5 and then subtract by 5 on both sides to get that y = 2x - 5. Next, we can substitute 2x - 5 in for y in the second equation because y = 2x - 5. We would get that 3x + 2x - 5 = -9, so 5x - 5 = -9, and if you add by 5 on both sides, you get 5x = -4. Finally, we can divide by 5 on both sides to get that x = -4/5. If you want to find y, we can find it by substituting x into the equation 2x - 5 = y. 2 * -4/5 - 5 is equal to y, so -8/5 - 5 = y, and lastly, y = -6 3/5